2012
DOI: 10.3346/jkms.2012.27.6.707
|View full text |Cite
|
Sign up to set email alerts
|

Amnesia and Pain Relief after Cardiopulmonary Resuscitation in a Cancer Pain Patient: A Case Report

Abstract: The mechanism of chronic pain is very complicated. Memory, pain, and opioid dependence appear to share common mechanism, including synaptic plasticity, and anatomical structures. A 48-yr-old woman with severe pain caused by bone metastasis of breast cancer received epidural block. After local anesthetics were injected, she had a seizure and then went into cardiac arrest. Following cardiopulmonary resuscitation, her cardiac rhythm returned to normal, but her memory had disappeared. Also, her excruciating pain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…25 Additionally, there are 2 case reports of 3 patients with diverse chronic pain conditions that after an episode of significant memory loss experience dramatic decrease in their pain and in opiate use. 7,9 Given our results, the simplest explanation for these cases is that the memory loss is primarily due to hippocampal damage, which leads to disrupting persistent pain-related memory circuitry and diminished pain decrease even after substantial recovery from the amnesia. More systematic studies along these lines are urgently needed.…”
Section: Discussionmentioning
confidence: 80%
“…25 Additionally, there are 2 case reports of 3 patients with diverse chronic pain conditions that after an episode of significant memory loss experience dramatic decrease in their pain and in opiate use. 7,9 Given our results, the simplest explanation for these cases is that the memory loss is primarily due to hippocampal damage, which leads to disrupting persistent pain-related memory circuitry and diminished pain decrease even after substantial recovery from the amnesia. More systematic studies along these lines are urgently needed.…”
Section: Discussionmentioning
confidence: 80%
“…For example, both mice and human subjects became hypersensitive to pain when tested in an environment previously associated with an aversive tonic pain experience ( 36 ). Clinical studies have reported that patients with chronic pain were suddenly relieved from chronic pain after amnesia (memory loss) ( 37 , 38 ). In itch studies, it has been demonstrated that merely thinking about itch can cause itch perception in patients with chronic itch, which rarely happens in healthy subjects ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…These shared areas were found in the same group of healthy participants who underwent conditions of dyspnea (breathlessness) and pain, including the insular cortex, ACC, amygdala and medial thalamus 44 . The insular cortex and ACC have been found to be related to affective processing of pain 45 46 47 as well as attention and memory relevant to pain processing 48 49 50 51 52 53 . Memory plays an important role, particularly in chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, localized micro-stimulation to the insular cortex during peripheral aversive stimulation leads to item-specific impairment of aversive memory reconsolidation, anterograde amnesia 52 . There are case reports that patients with chronic pain reported pain relief after sudden amnesia 48 54 . Taken together, these studies suggest that anterograde amnesia to aversive electrical stimulation could possibly be able to account for the observed BreEStim effects.…”
Section: Discussionmentioning
confidence: 99%